Nanoemulsion drug delivery system loaded with imiquimod: a QbD-based strategy for augmenting anti-cancer effects - Shital Tanaji Jadhav; Vijay Rajaram Salunkhe; Somnath Devidas Bhinge (SpringerOpen, 2023)
Abstract Background Skin cancer is becoming a public health concern due to increased exposure to environmental pollutants and UV rays, among other factors. In India, skin neoplasms constitute 2-3% of all human cancer cases, whereas in the USA, 2-3 million cases of non-melanoma skin cancer are reported annually. Various drugs are available in the market for treating skin cancer. Imiquimod (IMQ) is one such drug approved by the USFDA for managing basal cell malignancy, external genital warts, and actinic keratosis. The conventional dosage form of IMQ cream has several side effects that can lead to therapy interruption. Therefore, the present work aims to develop an IMQ nanoemulsion with improved solubility, in vitro drug release and stability. Nanoemulsion was formulated using oleic acid/rose oil, with polysorbate 20/propylene glycol selected as the oil phase and Smix, respectively. Optimization carried out using a 32 factorial design with the aid of a quadratic model. Characterization was conducted for parameters, namely viscosity, pH, drug content, globule size, zeta potential and entrapment efficiency. Thermodynamic stability studies were conducted to assess the stability of the formulation. Furthermore, the optimized system was subjected to TEM analysis, in vitro drug release and in vitro cytotoxicity assay (MTT assay). Results Nanoemulsions were found to be in the size range of 152.80-470.13 nm and exhibited a spherical shape. Zeta potential values ranged from − 28.93 to − 58.48 mV. DSC measurements indicated the complete solubilization of IMQ in the nanoemulsion system. The optimized formulation F1 displayed the following characteristics: a globule size < 200 nm, a zeta potential > − 55 mV, a polydispersity index < 0.2, % drug content of 102.89 ± 1.06, % entrapment efficiency of 97.59 ± 0.24, a pH of 4.77 ± 0.06, and a viscosity of 4.06 ± 0.06 poise. In vitro IMQ release studies of nanoemulsion and commercial cream showed approximately 70% and 34% drug release, respectively, at the end of 8 h. Moreover, the in vitro cytotoxicity assay depicted that F1 exhibited greater cytotoxic potential compared to the commercial formulation against the A431 cell line. Conclusion The present investigation showed a significant improvement in in vitro drug release of the BCS class IV drug IMQ and enhanced cytotoxic activity against cancerous cells. IMQ-loaded nanoemulsion represents a promising vehicle for delivering treatment to the skin for treating skin cancer. Graphical abstract